Розгортання базових станцій на багатосмугових вулицях з мультизв'язком всередині і між RAT з використанням міліметрових та субміліметрових хвиль - Лютий, А. О. (ХНУРЕ, 2025)
To mitigate the impact of disruptions caused by dynamic blockage of propagation paths in millimeter-wave (mmWave) systems, 3GPP has proposed multi-connectivity, where user equipment (UE) supports simultaneous connection to both a sub-6 GHz base station (BS) and a mmWave BS. We consider one of the most challenging prospective deployments—deployment on multi-lane streets with multi-connectivity within and between RATs.
Keywords: субміліметрові хвилі; розгортання базових станцій